(untitled) (Academicia Globe: Inderscience Research, 2022)
This article gives different ideas and analogies about the formation of musical taste and its importance in our lives. The formation of talent and musical taste is compared by simple mathematical operations. For a secondary school music teacher, the goal of a 7-year music lesson, created in the 1980s, is the opinion of mature educators to set a 7-year course for themselves.